Women's Creativity since the Modern Movement (1918-2018) Toward a New Perception and Reception - Franchini, Caterina; Maria Garda, Emilia; Seražin, Helena (ZRC SAZU, Založba ZRC, 2018)
Extensive work is a result of four year research within the international project Women's Creativity since the Modern Movement, and brings new insights into women in architecture, construction, design, urban planning and landscape architecture in Europe and in the rest of the world. It is divided into eight chapters that combine 116 articles on topics: A. Women's education and training: National and international mappings~B. Women's legacy and heritage: Protection, restoration and enhancement~C. Women in communication and professional networks~D. Women and cultural tourism~E. Women's achievements and professional attainments: Moving boundaries~F. Women and sustainability: City and Landscape~G. Women 'as subjects': Documentation, methodology, interpretation and enhancement~SG. Design drawings.